Evaluation of two functional CD24 polymorphisms in primary sclerosing cholangitis. (3rd May 2020) - Zhang, Chengcheng Christine; Voitl, Robert; Hippchen, Theresa; Weiss, Karl-Heinz; Sauer, Peter; Rupp, Christian
Abstract: Background: Primary sclerosing cholangitis (PSC) is a progressive liver disease and characterized by chronic inflammation, sclerosis and strictures of bile ducts. Several genetic risk factors might contribute to pathogenesis. Functional single nucleotide polymorphisms (SNPs) in the CD24 gene have been associated with the development of autoimmune and autoinflammatory diseases and might contribute to the susceptibility for inflammatory bowel disease (IBD). Aim: This retrospective study aimed to evaluate the impact of two functional CD24 SNPs on clinical features and disease progression in patients with PSC. Methods: A C to T coding polymorphism (rs8734) and a TG deletion in the 3´- untranslated region (rs3838646) were genotyped. The study cohort comprises of 359 PSC patients for rs3838646 genotype and 335 PSC patients for rs8734 genotype. Clinical and laboratory parameters were collected by chart review. Results: For the rs8734 genotype, 175 patients (52.2%) were found to be homozygous wildtype ('Ala/Ala'), 127 (37.9%) patients were heterozygous ('Ala/Val') and 33 patients (9.9%) were homozygous mutant ('Val/Val'). The rs8734genotype was associated with a decreased risk for dominant strictures at first diagnosis of PSC ( p = .04). For the rs3838646 genotype, 322 patients (89.7%) were found to be homozygous wildtype ('TG/TG'); 37 showed the 'TG/del' genotype (10.3%). The 'TG/del'genotype was associated with alower risk of IBD ( p = .01).There was no influence of both CD24 SNPs with clinical end points or transplantation-free survival in our PSC cohort. Conclusion: Our results suggest a mild association of the rs8734 CD24 genotype with dominant strictures at first diagnosis of PSC. The rs3838646 CD24 genotype is associated with a lower rate of IBD. Both SNPs seem to modulate the clinical phenotype without major pathogenetic importance for disease progression in PSC.